2014
DOI: 10.1124/mol.114.093393
|View full text |Cite
|
Sign up to set email alerts
|

Superiority of Combined Phosphodiesterase PDE3/PDE4 Inhibition over PDE4 Inhibition Alone on Glucocorticoid- and Long-Acting β2-Adrenoceptor Agonist–Induced Gene Expression in Human Airway Epithelial Cells

Abstract: Glucocorticoids, also known as corticosteroids, induce effector gene transcription as a part of their anti-inflammatory mechanisms of action. Such genomic effects can be significantly enhanced by long-acting b 2 -adrenoceptor agonists (LABAs) and may contribute to the clinical superiority of inhaled corticosteroid (ICS)/LABA combinations in asthma and chronic obstructive pulmonary disease (COPD) over ICSs alone. Using models of cAMP-and glucocorticoid-induced transcription in human bronchial epithelial BEAS-2B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 62 publications
3
42
0
Order By: Relevance
“…Furthermore, the use of salmeterol in the clinic is now strictly indicated for use as an add-on to therapy with steroids. It has been appreciated that use of PDE4 inhibitors in the treatment of asthma and chronic obstructive pulmonary disease may be clinically important and synergize with glucocorticoids and LABA treatment to reduce the frequency of exacerbations, as recently discussed (Kaur et al, 2008;Nino et al, 2010;Cooper et al, 2011;Holden et al, 2011;Dekkers et al, 2012;Manetsch et al, 2013;Moodley et al, 2013;Theron et al, 2013;Giembycz and Newton, 2014;BinMahfouz et al, 2015). Our findings showing the dramatic effects of PDE inhibition on cAMP levels after either long-term or short-term salmeterol treatment support the importance of developing multidrug therapy that includes PDE inhibitors, LABAs, and steroids.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Furthermore, the use of salmeterol in the clinic is now strictly indicated for use as an add-on to therapy with steroids. It has been appreciated that use of PDE4 inhibitors in the treatment of asthma and chronic obstructive pulmonary disease may be clinically important and synergize with glucocorticoids and LABA treatment to reduce the frequency of exacerbations, as recently discussed (Kaur et al, 2008;Nino et al, 2010;Cooper et al, 2011;Holden et al, 2011;Dekkers et al, 2012;Manetsch et al, 2013;Moodley et al, 2013;Theron et al, 2013;Giembycz and Newton, 2014;BinMahfouz et al, 2015). Our findings showing the dramatic effects of PDE inhibition on cAMP levels after either long-term or short-term salmeterol treatment support the importance of developing multidrug therapy that includes PDE inhibitors, LABAs, and steroids.…”
Section: Discussionsupporting
confidence: 53%
“…Furthermore, Billington et al (2008) reported that "elevation of cAMP within the cytoplasm after b2AR stimulation is rapid and shows no distinct spatial compartmentalization in HASM cells." In terms of downstream actions, BinMahfouz et al (2015) thoroughly investigated a spectrum of important downstream actions of LABAs using BEAS2B cells, particularly the roles of PDE3 and PDE4 inhibitors on the time dependence of PKA activation of cAMP response elementbinding protein and glucocorticoid regulation of glucocorticoid response elements. However, the authors did not investigate any of the efficacy and desensitization parameters that we examined in our study; nonetheless, the studies are remarkably complementary, although they used the LABA formoterol and not salmeterol.…”
Section: Discussionmentioning
confidence: 99%
“…It has a half-life (t½) of 11 hours (21,24) and was shown to be effective in an asthma model (7). PDE4 and combined PDE3/4 inhibition may enhance the effects of glucocorticoid treatment (26,27). Since the major action of RPL554 is PDE3 inhibition, it is important to know what the exact contribution of PDE3 is to allergic airway inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Even though RPL554 is considered as one of the most selective PDE3 inhibitors based on an about 3000× higher IC 50 value for purified human platelet PDE3 compared to neutrophil PDE4 (PDE3: 0.4 nM; PDE4:1479 nM) (Boswell‐Smith et al ., 2006), a growing body of evidence suggest that dual inhibition of PDE3 and PDE4, using higher levels of inhibitor (10 μM or 0.018 mg·kg −1 ), can more effectively induce bronchodilation with potential additive effects of suppressing release of inflammatory mediators (Calzetta et al ., 2013; Franciosi et al ., 2013). Moreover, dual inhibition of PDE3 and PDE4 sensitized cells to long acting β 2 ‐adrenoceptor agonists (LABAs) and corticosteroid (ICS)/LABA combinations, in cell‐based models (BinMahfouz et al ., 2015), indicating that dual inhibition of PDE3 and PDE4 acted as an add‐on effect to LABAs and ICS/LABA combinations, to further enhance their therapeutic benefits (Giembycz and Maurice, 2014). Here, we demonstrate that PDE3 activity, together with PDE4, is up‐regulated by exposure to CS.…”
Section: Discussionmentioning
confidence: 99%